Analyzing the determining factors of funding speed on equity crowdfunding - Ike Arisanti; Tri Wahyu Oktavendi (Jurnal Akuntansi dan Auditing Indonesia, 2022)
This research aimed to figure out the determining factors of funding speed on equity crowdfunding in Indonesia using a quantitative method. This research used the secondary data sourced from the equity crowdfunding platforms. The collected data were then analyzed using a statistical test instrument (STATA 15). The results showed that only project duration affected funding speed. Business Category, Gender, Yield, Equity Share, and Profitability did not affect Funding Speed. Thus, investors only paid attention to project duration. This research impacted fintech policy, especially on the importance of comprehensive information in the prospectus reports of fund-demanding parties.